2013
DOI: 10.1002/2013gl058114
|View full text |Cite
|
Sign up to set email alerts
|

Surface exchange between the Weddell and Scotia Seas

Abstract: Within Drake Passage, the southern flank of the Antarctic Circumpolar Current (ACC) hosts the ventilation of deep water, the injection of Antarctic shelf waters and interactions between westward and eastward boundary currents. This exchange is explored through the trajectories of forty surface drifters released in January 2012 in the northwestern Weddell Sea. The drifters detail Lagrangian transport pathways between the eastern Antarctic Peninsula and sites of elevated chlorophyll in the Scotia Sea. ACC fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The relative isolation of South Orkney Islands is corroborated by drifter data, which reveal a northward flow of Weddell Sea water across the South Scotia Ridge between Elephant Island and the South Orkney Islands, acting as a dynamic barrier to exchange between populations at the Antarctic Peninsula and South Orkney Islands (Thompson et al. ; Thompson and Youngs ).…”
Section: Discussionmentioning
confidence: 79%
“…The relative isolation of South Orkney Islands is corroborated by drifter data, which reveal a northward flow of Weddell Sea water across the South Scotia Ridge between Elephant Island and the South Orkney Islands, acting as a dynamic barrier to exchange between populations at the Antarctic Peninsula and South Orkney Islands (Thompson et al. ; Thompson and Youngs ).…”
Section: Discussionmentioning
confidence: 79%
“…As atmospheric deposition is limited in the HTV region [ Cassar et al ., ], the main iron sources are likely from ice melt and obduction of subsurface iron‐rich waters. In the Weddell Sea, studies have found that weakening winds can shift the boundary current toward shore, increasing the interaction between offshore waters and the shelf [ Thompson and Youngs , ; Youngs et al ., ]. In the WAP region, IAV in northerly wind strength could influence the extent of interactions of the boundary current with iron‐rich shelf waters.…”
Section: Discussionmentioning
confidence: 99%
“…1; Jiang et al 2013). In the BS, cold salty Weddell-shelf water enters near JI and flows south along the northern coast of the Antarctic Peninsula (von Gyldenfeldt et al 2002, Thompson et al 2009, Thompson & Youngs 2013. Water from the Antarctic Circumpolar Current (ACC; Bellings hausen surface water, and Upper Circumpolar Deep Water) enters the BS from the southwest at the surface and at mid-depths, and flows northeast along the southern coast of the South Shetland Islands (Gordon & Nowlin 1978, Gordon et al 2000.…”
Section: Study Areamentioning
confidence: 99%